Cutaneous and renal glomerular vasculopathy as a cause of acute kidney injury in dogs in the UK. (11th April 2015) - Holm, L. P.; Hawkins, I.; Robin, C.; Newton, R. J.; Jepson, R.; Stanzani, G.; McMahon, L. A.; Pesavento, P.; Carr, T.; Cogan, T.; Couto, C. G.; Cianciolo, R.; et al.
Abstract : To describe the signalment, clinicopathological findings and outcome in dogs presenting with acute kidney injury (AKI) and skin lesions between November 2012 and March 2014, in whom cutaneous and renal glomerular vasculopathy (CRGV) was suspected and renal thrombotic microangiopathy (TMA) was histopathologically confirmed. The medical records of dogs with skin lesions and AKI, with histopathologically confirmed renal TMA, were retrospectively reviewed. Thirty dogs from across the UK were identified with clinicopathological findings compatible with CRGV. These findings included the following: skin lesions, predominantly affecting the distal extremities; AKI; and variably, anaemia, thrombocytopaenia and hyperbilirubinaemia. Known causes of AKI were excluded. The major renal histopathogical finding was TMA. All thirty dogs died or were euthanised. Shiga toxin was not identified in the kidneys of affected dogs. Escherichia coli genes encoding shiga toxin were not identified in faeces from affected dogs. CRGV has previously been reported in greyhounds in the USA, a greyhound in the UK, without renal involvement, and a Great Dane in Germany. This is the first report of a series of non‐greyhound dogs with CRGV and AKI in the UK. CRGV is a disease of unknown aetiology carrying a poor prognosis when azotaemia develops.